Analisis Lalu Lintas Data Internet Gim Multipemain Battle Royale Berbasis Konsol di Jakarta - Solihin, Unang; Djajasoepena, Rafie (INTEK : Jurnal Informatika dan Teknologi Informasi, 2023)
Playing games on portable or non-portable console platforms is an activity that can be done anywhere when having free time. However, playing online-based games requires reliable Internet speed in Jakarta, both wired and wireless, in several areas, specifically in multiplayer online games like Fortnite, which are busy playing multi-platforms. This study aims to determine Internet data traffic when playing in 1 match. This research activity was carried out using quantitative methods, measured descriptively, using non-probabilistic samples, and using primary data that was recorded and worked on independently. Obtained in 1 time playing the game Fortnite has an average downstream of 10.52 ± 4.41 KBps, upstream of 3.08 ± 1.12 Kbps, ping of 103.44 ± 10.74 milliseconds, and 0% packet loss. Data traffic, which is only 0.12% downstream and 0.04% upstream, shows that this game is friendly to Internet data traffic to be played on game consoles using a postpaid cable network in Jakarta.